Real-time observation of X-ray-induced intramolecular and interatomic electronic decay in CH2I2 - Fukuzawa, Hironobu; Takanashi, Tsukasa; Kukk, Edwin; Motomura, Koji; Wada, Shin-ichi; Nagaya, Kiyonobu; Ito, Yuta; Nishiyama, Toshiyuki; Nicolas, Christophe; Kumagai, Yoshiaki; Iablonskyi, Denys; Mondal, Subhendu; et al. (My University, 2019)
The increasing availability of X-ray free-electron lasers (XFELs) has catalyzed the development of single-object structural determination and of structural dynamics tracking in real-time. Disentangling the molecular-level reactions triggered by the interaction with an XFEL pulse is a fundamental step towards developing such applications. Here we report real-time observations of XFEL-induced electronic decay via short-lived transient electronic states in the diiodomethane molecule, using a femtosecond near-infrared probe laser. We determine the lifetimes of the transient states populated during the XFEL-induced Auger cascades and find that multiply charged iodine ions are issued from short-lived (∼20 fs) transient states, whereas the singly charged ones originate from significantly longer-lived states (∼100 fs). We identify the mechanisms behind these different time scales: contrary to the short-lived transient states which relax by molecular Auger decay, the long-lived ones decay by an interatomic Coulombic decay between two iodine atoms, during the molecular fragmentation.